A chitosan–polypyrrole@Fe3O4 nanocomposite for magnetic solid-phase extraction of macrolides from swine urine samples. Issue 6 (26th February 2015) - Liao, Qie Gen; Hu, Li Fang; Luo, Lin Guang
Abstract : An effective MSPE procedure with the CS–PPy@Fe3 O4 nanocomposite has been developed for extraction of four macrolides. An effective MSPE-LC-MS/MS method for determination of macrolides in swine urine samples has been developed. Abstract : In this paper, a new method was established for the determination of four macrolides (azithromycin, roxithromycin, clarithromycin and tylosin tartrate) from swine urine samples by magnetic solid-phase extraction coupled with liquid chromatography tandem mass spectrometry. The extraction adsorbent was synthesized to form a chitosan–polypyrrole (CS–PPy)@Fe3 O4 core–shell magnetic nanocomposite. The main factors influencing the extraction efficiency including the amount of adsorbent, solution pH, extraction time, and volume of desorption solution were studied and optimized. Under the optimal conditions, recoveries of the spiked samples ranged from 76 to 84% with the relative standard deviations lower than 10%. The limits of detection ranged from 0.04 to 0.2 μg L −1 for azithromycin, roxithromycin, clarithromycin and tylosin. The proposed method was successfully applied for selective and efficient determination of macrolides from swine urine samples.